Volumetric properties and abrasion resistance of stone mastic asphalt incorporating eggshell powder - Putra Jaya, Ramadhansyah; K. A., Masri; E., Ganesan; Doh, Shu Ing; Jasni, N. E.; AlSaffar, Z. H.; Mohammed, A. A. (IOP Publishing Ltd, 2021)
Stone Mastic Asphalt (SMA) is designed to improve durability and life span of road pavement through the use of a stable stone-on-stone skeleton held together by a rich mixture of asphalt. However, over time the structure is subjected to damage from cracking, rutting, stripping and rapid aging under the effects of repeated vehicle loading, hot climates and heavy rainfall. Previous studies proved that eggshell is capable to enhance the strength and durability of concrete. Thus, the aim of this study is to evaluate the performance of these stone mastic asphalt mixtures with the eggshell powder and overcome the issue that is related to SMA. A mixture contains varying percentages of eggshell powder were assessed to check which samples gives the best performance as per the requirement by using laboratory tests which are LA Abrasion and volumetric properties. Results indicated that eggshell powder can effectively recover and enhance abrasion resistance of asphalt and increases the marshal stability of SMA. SMA mixtures modified with eggshell powder produce the performance enhancement of SMA as a road surfacing material. It is concluded that the asphalt mixtures containing eggshell powder could be increases the stability and strength of the mix.